Rich Dykes from L.A. are called Lesbians - Anne Crémieux (TV Series, 2013)
“Have you ever thought about suing The L Word crew for stealing so many of your ideas?” writes DeLandDeLakes on the blog of Alison Bechdel, the creator of Dykes to Watch Out For. Another blogger described DTWOF as “The L Word, in comic strip form, before The L Word ever existed.” I would like to present how The L Word does indeed share quite a few traits with DTWOF. Indeed, both series portray a group of lesbian friends who live the lesbian life, speak about and experience such community events as gay pride or lesbian cruises, have babies through artificial insemination, and famously set up charts to keep track of reported sexual encounters. In both cases, the serial form allows for strong identification with diverse characters, who present conflicting takes on gender and sexuality, personal and political ethics. One major element, however, is the difference in medium and audience range. As a comic strip published exclusively in underground, queer magazines, Bechdel’s series never reached the mainstream audience The L Word had to seduce to survive its first season on Showtime. The two series offer different approaches to American late 20th c. / early 21st c. lesbian culture, showing how targeting a much broader TV audience might have resulted in a slightly different depiction of how women navigate their gender and sexuality to self-identify as lesbians, rather than dykes.